2020
DOI: 10.1136/gpsych-2020-100311
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use and repeated attempted suicide among senior high school students in Ghana: Evidence from the WHO Global School-Based Student Health Survey, 2012

Abstract: BackgroundThe association between substance use including marijuana use and attempted suicide has been well documented. However, little is known about marijuana use and its association with attempted suicide repetition among young people in low-income and middle-income contexts.AimsThis analysis was conducted to assess the factors associated with marijuana use and ascertain marijuana use as a determinant of repeated attempted suicide among senior high school (SHS) students in Ghana.MethodsData from the 2012 Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
(27 reference statements)
5
11
1
Order By: Relevance
“…In assessing repeated attempted suicide, this study adopted a similar method employed to assess the association between marijuana use and repeated attempted suicide among senior high school students in Ghana. 23 The previous study reported a 12-month prevalence estimate of repeated attempted suicide to be 11.5%—nearly 2 times the estimate reported by this study. Interestingly, this study has also shown a relatively higher prevalence estimate in West Africa (10.1%), where Ghana is located.…”
Section: Discussionsupporting
confidence: 47%
See 4 more Smart Citations
“…In assessing repeated attempted suicide, this study adopted a similar method employed to assess the association between marijuana use and repeated attempted suicide among senior high school students in Ghana. 23 The previous study reported a 12-month prevalence estimate of repeated attempted suicide to be 11.5%—nearly 2 times the estimate reported by this study. Interestingly, this study has also shown a relatively higher prevalence estimate in West Africa (10.1%), where Ghana is located.…”
Section: Discussionsupporting
confidence: 47%
“…Generally, whereas marijuana use has been found to worsen negative mental health outcomes and symptoms, including depression, 46 47 there is still limited evidence, particularly, from Africa regarding the association between marijuana use and suicidal behaviour, especially, repeated attempted suicide. 23 48 Evidence of a recent meta-analysis 48 and an earlier longitudinal study 49 suggests that chronic marijuana use represents a risk factor for death by suicide, while frequent use of marijuana presents as a risk factor for a daily experience of suicidal ideation. 50 51 Suicides among adolescents have a variety of causes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations